TRPV3 in Drug Development - Lisa M. Broad; Adrian J. Mogg; Elizabeth Eberle; Marcia Tolley; Dominic L. Li; Kelly L. Knopp (MDPI AG, 2016)
Transient receptor potential vanilloid 3 (TRPV3) is a member of the TRP (Transient Receptor Potential) super-family. It is a relatively underexplored member of the thermo-TRP sub-family (Figure 1), however, genetic mutations and use of gene knock-outs and selective pharmacological tools are helping to provide insights into its role and therapeutic potential. TRPV3 is highly expressed in skin, where it is implicated in skin physiology and pathophysiology, thermo-sensing and nociception. Gain of function TRPV3 mutations in rodent and man have enabled the role of TRPV3 in skin health and disease to be particularly well defined. Pre-clinical studies provide some rationale to support development of TRPV3 antagonists for therapeutic application for the treatment of inflammatory skin conditions, itch and pain. However, to date, only one compound directed towards block of the TRPV3 receptor (GRC15300) has progressed into clinical trials. Currently, there are no known clinical trials in progress employing a TRPV3 antagonist.